Формирование обобщенных представлений о животных в дошкольном возрасте - Бекмурзина, Ж.М. (My University, 2013)
In article problems of formation of general concepts and concepts about animals at preschool children are covered. Features of classification, and also ways of generalization of concrete knowledge of animals at preschool age reveal.